Knowledge sharing on best practices for managing crop genebanks - Jorge, M.A.B.; Claessens, G.; Hanson, Jean; Dulloo, Mohammad Ehsan; Goldberg, E.D.; Thormann, I.; Alemayehu, S.; Gacheru, E.; Amri, A.; Benson, E.; Dumet, D.; Roux, N.; et al. (2010)
The Crop Genebank Knowledge Base (CGKB) is an initiative of the Consultative Group of International Agriculture Research (CGIAR) System-wide Genetic Resources Programme (SGRP). The CGKB was created for sharing knowledge about best practices for managing plant genetic resources (PGR), and making effective decisions about genebank management. Genebank practices from CGIAR Centers and national genebanks were gathered for nine crops (banana, barley, cassava, chickpea, forage grasses and legumes, maize, rice and wheat). This information will help PGR professionals to participate in a global crop conservation effort. An interactive approach with many partners and stakeholders was used to gather published and unpublished information about genebank management. Information on crop-specific best practices was initially collected from crop experts using pre-defined forms. In parallel, a web portal was developed using the open-source content management system (CMS) Joomla!. The CMS allows several editors to maintain pages and update them. Other participatory tools such as wiki pages, a blog, a discussion forum and online forms have been set up to gather future contributions, including information on other crops. The site provides a one-stop platform for information on conservation, characterization, regeneration and safety duplication of each of the nine crops. It also provides information on general (non-crop-specific) genebank management procedures, as well as a comprehensive bibliography of online publications, a glossary, links to relevant external websites, video and photo materials, and training modules. This paper discusses a process of collective action to develop a multi-institutional web platform, highlights important criteria for success, challenges and major lessons learned, and proposes options for the way forward.